Evaluation of the INNOVANCE PFA P2Y assay and its association with CYP2C19 genotypes. (11th March 2014) - Kim, Hyunjung; Kim, Yonggoo; Koh, Yoon-Seok; Lee, Hae Kyung; Chae, Hyojin; Jekarl, Dong Wook; Lee, Jong-Min; Shin, Woo-Seung; Kim, Tae-Hoon
Abstract: The purpose of this study was to evaluate associations between INNOVANCE PFA P2Y (PFA P2Y) test results and CYP2C19 genotypes and provide baseline data for PFA P2Y testing to establish a therapeutic monitoring strategy for clopidogrel. A total of 75 new patients with acute coronary syndrome with planned percutaneous coronary intervention were enrolled between June 2012 and September 2012. All patients received clopidogrel at an initial loading dose of 600 mg followed by a 75-mg daily maintenance dose. Blood samples were obtained on the third morning after clopidogrel loading. PFA P2Y, VerifyNow P2Y12 and VASP assays were used to determine platelet inhibition due to clopidogrel, and the Verigene CYP2C19 test was used for CYP2C19 genotyping. The genotype frequency of 75 patients was as follows: CYP2C19 *1/*1 (wild type), 28 (37.3%); *1/*2, 31 (41.3%); *1/*3, 4 (5.3%); *2/*2, 5 (6.7%); *2/*3, 5 (6.7%); *1/*17, 1 (1.3%); and *2/*17, 1 (1.3%). Classified according to CYP2C19 genotypes, there were 29 (38.7%) extensive metabolizers (EM) or ultra rapid metabolizers (UM), 35 (46.7%) intermediate metabolizers (IM), and 10 (13.3%) poor metabolizers (PM). Median (interquartile range) PFA P2Y closure times (seconds) were 119 (101–260), 300 (130–300) and 300 (300–300) in the PM, IM and EM or UM groups, respectively ( p < 0.05). Median (interquartile range) VerifyNow PRUs were 294 (213–297), 215 (165–320) and 189 (118–279); and the VASP platelet reactivity index (%) was 52.7 (33.3–91.9), 59.9 (41.4–72.8) and 38.9 (26.8–62.2) in the PM, IM and EM or UM groups, respectively ( p > 0.05). Compared with non-carriers, carriers of reduced function CYP2C19 alleles tended to have higher platelet reactivity after clopidogrel treatment. The cut-off for PM versus other groups (IM and EM or UM) was ≤141 seconds (AUC 0.704, sensitivity 70%, specificity 76.6%) on the ROC curve. A statistically significant correlation between PFA P2Y (seconds) and VerifyNow (PRU) was found (ρ = −0.47, p < 0.0001). In conclusion, the PFA P2Y test showed a statistically significant association with CYP2C19 metabolizer phenotypes based on CYP2C19 genotyping and effectively determined the risk groups resistant to clopidogrel therapy, including PM.